Pulmonary dysfunction in obese early adolescents (Medical Journal of Indonesia, 2010)
Aim Obesity leads to various complications, including pulmonary dysfunction. Studies on pulmonary function of obese children are limited and the results are controversial. This study was aimed to determine proportion of pulmonary dysfunction on early adolescents with obesity and to evaluate correlation between obesity degree with pulmonary dysfunction degree. Methods A cross-sectional study was conducted at the Department of Child Health, Medical School, University of Indonesia, from November 2007 to December 2008. Subjects were 10 to 12 year-old adolescents with obesity. Subjects underwent pulmonary function test (PFT) to assess FEV1/FVC, FEV1, FVC, V50, and V25. Results 110 subjects fulfilled study criteria, 83 (75.5%) were male and 27 (24.5%) were female with median BMI 26.7 (22.6-54.7) kg/m2; 92 subjects (83.6%) were superobese. History of asthma and allergic rhinitis were found in 32 (29.1%) and 46 (41.8%) subjects, respectively. 64 (58.2%) subjects had abnormal PFT results consisting of restrictive type in 28 (25.5%) subjects, obstructive in 3 (2.7%), and combined type in 33 (30%). Mean FEV1, FVC, V50, and V25 values were below normal, while mean FEV1/FVC ratio was normal. There was no statistically significant correlation between BMI and PFT parameters. No significant correlation was found between degree of obesity and the severity of pulmonary dysfunction. Conclusions Pulmonary dysfunction occurs in 58.2% obese early adolescents. The most common abnormality was combined type (30%), followed by restrictive (25.5%), and obstructive type (2.7%). There was no correlation between BMI and pulmonary function test parameters. (Med J Indones 2010;19:179-84)